Scientific Publication and Dissemination in Times of a COVID-19 Pandemic - Guzmán-Useche, Eliana (2020)
In this global pandemic, scientific production and dissemination has allowed the creation of reliable knowledge bases, in search of common purposes: eradicate the virus, prevent new infections and determine public health strategies for the immediate future.